Handbook on household hazardous waste - Cabaniss, Amy (Bernan, 2018)
Household hazardous waste (HHW) is a topic that affects every individual and community given the nearly universal use, storage, and disposal of chemical consumer products. Yet many communities lack the basic information, guidance, and planning support for HHW collection and management so that struggles (e.g., to gain politicians’ and residents’ support, host a collection, build a facility, affect behavior change, and encourage extended producer responsibility) continue on a regular basis. This book is for professionals, students, government officials and others interested in HHW and accommodating the increasing societal demand for this disposal option. In the evolving field of HHW collection and management, this book: provides an unparalleled, comprehensive look at household hazardous wasteis a must-have for anyone interested in the solid waste management field, whether novice or experienced, because of the valuable overview and specifics it provides for addressing the ubiquitous issue of HHWoffers perspectives based on many collective years of experts’ accrued insightthe chapters are written by leading practitioners and visionariesis packed with useful information on many aspects of HHW including its definition, mechanisms for collection and creative collection options, tools for behavior change, and product stewardshipoffers an extensive resource list for more information. Much has changed in 10 years since the first edition appeared, and each chapter in the Handbook on Household Hazardous Waste, Second Edition, is updated to reflect changes and advances in the field of HHW collection and management. This includes updated appendices and the extensive resource list.
Keywords: dept.mgt